2019
DOI: 10.1186/s12936-019-2934-4
|View full text |Cite
|
Sign up to set email alerts
|

Pairwise growth competitions identify relative fitness relationships among artemisinin resistant Plasmodium falciparum field isolates

Abstract: Background Competitive outcomes between co-infecting malaria parasite lines can reveal fitness disparities in blood stage growth. Blood stage fitness costs often accompany the evolution of drug resistance, with the expectation that relatively fitter parasites will be more likely to spread in populations. With the recent emergence of artemisinin resistance, it is important to understand the relative competitive fitness of the metabolically active asexual blood stage parasites. Genetically distinct … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

1
52
0

Year Published

2019
2019
2023
2023

Publication Types

Select...
6
2

Relationship

4
4

Authors

Journals

citations
Cited by 33 publications
(53 citation statements)
references
References 45 publications
(75 reference statements)
1
52
0
Order By: Relevance
“…PfK13 mutations have been shown to incur a fitness cost on the parasites, manifested as lower growth rates as well as reduced fitness in an in vitro growth competition assay, as summarized in Table S4 in the supplemental material (57,67,68). Different PfK13 alleles show considerable variations in their impact on parasite fitness, which appear to be governed by the genetic backgrounds of the strains.…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…PfK13 mutations have been shown to incur a fitness cost on the parasites, manifested as lower growth rates as well as reduced fitness in an in vitro growth competition assay, as summarized in Table S4 in the supplemental material (57,67,68). Different PfK13 alleles show considerable variations in their impact on parasite fitness, which appear to be governed by the genetic backgrounds of the strains.…”
Section: Discussionmentioning
confidence: 99%
“…Straimer et al found the C580Y mutation to be fitness neutral in recent Cambodian field isolates compared to the effect of the R539T or I543T mutation, whereas the C580Y mutation exerted much higher growth disadvantages in a strain that was culture adapted in 1976, long before ART deployment (57). Two later studies determined that the C580Y mutation carries a greater competitive fitness burden than other PfK13 alleles tested in field isolates obtained from the Thailand-Myanmar border area in 2008 and 2011, respectively (67,68). Interestingly, the C580Y isolate obtained in 2011 is a clinically resistant parasite strain with a long parasite clearance half-life of 7.84 h (67).…”
Section: Discussionmentioning
confidence: 99%
“…Issues with gamete recognition and compatibility might drive segregation distortion observed on chromosome 13 in NF54 x NHP4026 and 7G8 x GB4 (both allopatric) but not in the sympatric MKK2835 x NHP1337 cross (see also [33]). Performing competition experiments between individual progeny with different alleles at these distorted and selected loci will be informative in determining how different combinations of alleles might contribute to parasite fitness [45]. These experiments can be followed with CRISPR/Cas9 editing of polymorphisms in individual genes as further validation.…”
Section: Discussionmentioning
confidence: 99%
“…The most highly distorted subregion on chromosome 7 (predominantly inherited from the NF54 parent with only 3 progeny inheriting alleles from NHP4026) includes pfcrt which is known to carry a substantial fitness cost in some genetic backgrounds and that different combinations of mutations are more deleterious than others [31]. Although NHP4026 is a parasite that grows particularly well in in vitro culture [45] (even outcompeting NF54 in co-culture experiments) it is clear that inheriting an NHP4026 allele at this locus contributes a fitness cost. The most highly skewed subregion on chromosome 14 is also predominantly inherited from NF54 and contains pfarps2 which has been associated with artemisinin resistance (slow clearance of parasite from treated patients) in GWAS studies and is thought to contribute to a permission background for development of artemisinin resistance [7].…”
Section: Discussionmentioning
confidence: 99%
“…It is essential that the parasites are tightly synchronized in order to assay during the short window (0-3 h) that can differentiate ART resistant parasites from ART sensitive parasites. To do this, both a Percoll gradient and sorbitol are typically used (8), but several alterations have been attempted to increase the throughput of the assay such as using both sorbitol and magnet columns (12), using syringe filters to select for merozoites (13), and using a dual layer Percoll gradient, as has been done previously in other malaria assays (14,15). Another major bottleneck and source of variability in the final readout of the RSA is counting viable malaria parasites by microscopy (8,11,14).…”
Section: Introductionmentioning
confidence: 99%